The Caribbean and the Atlantic World Economy
XIV, 319 p.
Keywords: This collection of essays explores the inter-imperial connections between British, Spanish, Dutch, and French Caribbean colonies, and the 'Old World' countries which founded them. Grounded in primary archival research, the thirteen contributors focus on the ways that participants in the Atlantic World economy transcended imperial boundaries.